Exercise Tolerance Test Examination for Determination of Obesity Paradox in Patients with Systolic Heart Failure. A Clinical Comparative Study - Omer Aziz Mirza, Zahoor Khan, Fareha Kashan Theba, Iftikhar Ahmed, Hira Riaz, Misdaq Batool, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: Current study was conducted in Department of cardiology, Hayatabad medical complex Peshawar, for one year of duration. The aims and objective of this study was to deliver health awareness and description of a biological hypothesis i.e. obesity paradox, among our community. Methodology: 250 patients with a history of cardiac complications were selected and divided into two different groups. 100 individuals with BMI > 25 were in group A and their history of systolic heart failure was positive while in Group-B 150 patients with BMI< 35 were selected and their systolic heart failure history were negative. Conclusion: Obesity paradox provides survival against systolic heart failure in high BMI cardiac patients this was the findings of this study. On the other side cardiorespiratory fitness also play an important role in severity, and survival. It has seen that obesity was found protective in cardiac diseases and there is a strong relationship between body mass index and obesity paradox in heart failure. The standard mean deviation levels of BMI, systolic blood pressure, percentage of ECG variation, oxygen saturation of exercise tolerance test were significant (P<0.005) in group-B as compared to the group-A.